Hands-On Microsoft Teams - Second Edition - Ferreira, João (Packt Publishing, 2021)
Harness the power of Teams to improve enterprise productivity and engagement Key Features Updated with new chapters on Teams templates, the special editions of Teams, and Microsoft Viva Customize Teams for increased efficiency, collaborate with best practices, and use advanced Teams functionalities to your advantage Extend Teams through integration with Microsoft services such as PowerShell, SharePoint, Power Apps, and Power Automate Book Description Microsoft Teams is your entry point to communication and collaboration in the modern workplace. In Hands-On Microsoft Teams, experienced Microsoft 365 certified professional Joao Ferreira shows you how to use Microsoft Teams to its full potential through practical tutorials. This guide to mastering Teams explores the platform in comprehensive detail and how it interacts with the rest of the Microsoft ecosystem to help you work efficiently and manage your resources. You'll get to grips with core functionality like setting up and managing teams, channels, chats, tabs, and meetings. You'll also learn to get the best out of Teams by adding custom apps, integrating with Microsoft 365, using PowerShell automation, and exploring useful settings you didn't know existed. Along the way, you'll be shown various real-world scenarios and how to implement solutions for them in Teams that will increase your productivity. Whether you're an administrator, manager, or team member, by the end of this book you'll be confident in using everything Microsoft Teams has to offer. What you will learn Perform scheduling and manage meetings, live events, and webinars Create and manage Microsoft Teams templates to streamline company processes Deal with permissions and security issues in managing private and public teams and channels Extend Microsoft Teams using custom apps, Microsoft 365, and PowerShell automation Build your own Teams app with The Developer Portal without writing any code Deploy helpful chatbots using QnA Maker and Power Virtual Agents Explore Teams use cases for education, frontline work, and personal life Bring together knowledge, learning, resources, and insights with the new employee experience platform, Microsoft Viva Who this book is for This Microsoft Teams book is for business professionals looking to use Teams for improving collaboration in an enterprise environment. The book will also be useful for Microsoft 365 administrators interested in implementing Microsoft Teams effectively.